An Enhanced Deep Learning & Artificial Intelligence Vehicle Detection Method From Unmanned Aerial Vehicles Imagery - Prof Veena Kiragi, Prof Anita Sharma (International Journal of Advanced Science and Technology, 2019)
For the use in many applications like civil, recreational and commercial areas, military due to indoor and outdoor use, vertical takeoff and vertical landing and high maneuverability the unmanned aerial vehicles are becoming popular platform for research. It has been developing very powerful, light and small embedding systems in recent innovations. For detecting the vehicles by integrating these types of embedding systems many real time applications can run on platform of unmanned aerial vehicle [1]. In this paper it studies the Deep Learning method for detecting the vehicles from unmanned aerial vehicle imaginary.